When one port does not return blood: two case reports of rare causes for misplaced central venous catheters - Pereira,Sandra (2016)
We present two cases of misplaced central venous catheters having in common theabsence of free blood return from one lumen immediately after placement. The former is acase of right hydrothorax associated with central venous catheterization with the catheter tipin intra-pleural location. In this case the distal port was never patent. In the latter case therewas an increased aspiration pressure through the middle port due to a catheter looping.The absence of free flow on aspiration from one lumen of a central catheter should not beundervalued. In these circumstances the catheter should not be used and needs to be removed.